Class Reservation Application - Rikip Ginanjar; Alvin Halim (IT for Society, 2018)
Many student do class reservation for their own problem in the class either the lecturer or the student itself that do the reservation. In president university class reservation become one of the important system that exist in the university organization system to service of unanticipated extra schedule for the sake of class session. No wonder in one day so many student do the class reservation but wasting time because of complicated process of the reservation and also manual process that annoying especially for student. The university have computerized system for everything process in the university but not this simple one yet important.  Many student always wasting time for only booking one class room that disturbing their activity because of the manual paper administration. The academic still use paper and find manually when they want to search empty room or checking room of some lecturer, because of this there happen so many times of miss information and communication that caused by negligance of the staff. We cannot hope them to do everything perfect because human can do some wrong too because of imperfectness that is why we need another solution for this to solve the problem.